Aptamer-based determination of ATP by using a functionalized impedimetric nanosensor and mediation by a triangular junction transducer - Gopinath, S.C.B. (Springer-Verlag Wien, 2017)
The authors describe an impedimetric nanosensor for aptamer-mediated detection of ATP. A triangular junction of polysilicon substrate is used as a transducer. The aptamer was immobilized on the substrate via biotin-streptavidin interaction. ATP can be detected by this method in the 10 to 100 nM concentration range at room temperature and estimated the signal to noise ratio above the range of 3σ. It was applied to the detection of ATP in 1:1000 diluted human urine. The desired transducer is highly reproducible and specific. It is selective over closely related molecules such as guanosine triphosphate, cytidine triphosphate and uridine triphosphate. The method is perceived to represent a valuable tool for the diagnosis for infections and inflammations. The novelties shown in this study compared to other sensors are, consumption of low sample volume (~ 1 μl), non-invasive and suitable with AC and DC currents. Figure not available: see fulltext.. © 2017, Springer-Verlag GmbH Austria.